Integrated Theory and Crimes of Trust - Menard, Scott W. (Journal of quantitative criminology, 2012)
The integrated theory first proposed by Elliott et al. ( 1979 ), combining strain, social control, and social learning (and sometimes social disorganization) theories, has been repeatedly tested and consistently supported for a wide range of behaviors including licit and illicit substance use, violence, and other forms of illegal behavior. It has not, however, been tested for a class of illegal behaviors best described as crimes of trust, which include different types of fraud, workplace theft, and income tax evasion. This category of offending includes offenses commonly regarded as white collar crime, and also offenses that have been more or less marginal to the study of white collar crime. The present paper tests the integrated theory specifically for crimes of trust in the National Youth Survey Family Study, a national, multigenerational sample of individuals whose focal respondents were 11–17 years old in 1976–1977, and who are now in middle adulthood. Relying on structural equation modeling (SEM), parallel tests are performed for two generations, the focal respondents in early middle age (ages 38–45) and their adult offspring (ages 18–24) for the period 2002–2004.